PERILAKU MASYARAKAT PENGENDARA BERMOTOR TERHADAP POTENSI KECELAKAAN LALU LINTAS DI KABUPATEN MAJENE PROVINSI SULAWESI BARAT - Magfirah, Magfirah; Qamariah S, Nur (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to provide knowledge about the effect of motorized driver bahavior on the potential of community traffic accidents in Majene district by using five variables: switching lanes without turn signal, driving while calling, breaking traffic signs, driving while listening to music and driving at high speed.This research was conducted in Majene district, West Sulawesi Province. This Study population is a community of motor vehicle users who are domiciled in Majene Regency. Sample was selected using a Likert scale. Data collection is done by observation techniques, interviews and through questionnaires. Data were analyzed using percentages and linear regression. The results of the study showed that the variable switching lanes without cents, driving while calling and driving while listening to music did not affect the potential for accidents while violating traffic signs and driving at high speed significantly influences the potential of traffic accidents.